10‐1: Layout of 1.50‐inch, 3207‐ppi OLED Display with OSLSI/SiLSI Structure Capable of Division Driving Fabricated through VLSI Process with Side‐by‐Side Patterning by Photolithography. Issue 1 (28th June 2022) - Saito, Toshihiko; Mizuguchi, Toshiki; Okamoto, Yuki; Ito, Minato; Toyotaka, Kouhei; Kozuma, Munehiro; Matsuzaki, Takanori; Kobayashi, Hidetomo; Onuki, Tatsuya; Hiura, Yoshikazu; Hodo, Ryota; Sasagawa, Shinya; et al.
Abstract : We fabricated a 1.50‐inch, 3207‐ppi OLED display with drivers capable of 32‐division driving, which is achieved by monolithically stacking OSFETs over SiFETs. Taking advantages of minute OSFETs with a high withstand voltage, Si‐OS connection regions were provided in subpixels to connect Si drivers and OS pixel arrays at given positions.